Unbalanced Response Analysis and Experiment of Magnetic Levitation Rotor Based on the State-Space Method - ZHANG, Shuyue; ZHANG, Yahu; LV, Xiaolian; JIN, Songling (Engineering Transactions, 2024)
Magnetic levitation compressors are critical for producing large flow rates of superfluid helium. The steady operation of these compressors depends heavily on the unbalanced response characteristic of their rotors. Previous research, utilizing traditional unbalance response calculation methods, primarily focused on displacement response while neglecting current response. This paper transforms the finite element model of the magnetic levitation rotor into a statespace representation. It then investigates the influence of vital parameters on both displacement and current responses. The results of speed-up experiment carried out on the compressor prototype test rig agree with the simulation results. The study indicates that adjusting control parameters can suppress vibration and simultaneously reduce control current. This work is essential for the application of compressors in the superfluid helium system.